Understanding Juvenile Delinquency: Exploring Theoretical Frameworks and Implications for Intervention - Majeed, Mudassir; Imran, Khadeeja; Ali, Asad (Annals of Human and Social Sciences, 2024)
The multifaceted nature of juvenile delinquency, encompassing behaviors that contravene societal norms and laws among individuals under 18. Influenced by factors at individual, familial, societal, and environmental levels, juvenile delinquency presents significant challenges globally. The theoretical frameworks such as anomie theory, subculture theory, and differential opportunity theory, shedding light on the underlying mechanisms driving delinquent behavior through descriptive research methodology. Despite extensive research, there remains a gap in understanding the nuanced interplay of these factors, necessitating a comprehensive synthesis and evaluation of existing frameworks. This framework is important for developing effective prevention and intervention strategies informed by these theories to address juvenile delinquency and promote positive youth development. Ultimately, a holistic approach integrating theory-driven insights with practical interventions is crucial for combating juvenile delinquency and enhancing the well-being of youth in society. Theories of juvenile delinquency provide frameworks for understanding and predicting behavior patterns among young people. This predictive ability can guide law enforcement, social workers, and educators in identifying individuals who may be at risk of engaging in delinquent behavior.